2015
DOI: 10.1128/jvi.02328-14
|View full text |Cite
|
Sign up to set email alerts
|

Malawi Polyomavirus Is a Prevalent Human Virus That Interacts with Known Tumor Suppressors

Abstract: h Malawi polyomavirus (MWPyV) is a recently identified human polyomavirus. Serology for MWPyV VP1 indicates that infection frequently occurs in childhood and reaches a prevalence of 75% in adults. The MWPyV small T antigen (ST) binds protein phosphatase 2A (PP2A), and the large T antigen (LT) binds pRb, p107, p130, and p53. However, the MWPyV LT was less stable than the simian virus 40 (SV40) LT and was unable to promote the growth of normal cells. This report confirms that MWPyV is a widespread human virus ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
1
21
1
Order By: Relevance
“…Seroprevalence to MWPyV (84.4%) was the second highest from all of HPyVs tested. Two recent studies reported MWPyV 42–75% in adulthood [Nicol et al, ; Berrios et al, ], which is slightly lower number compared to our findings. Seroprevalence to KIPyV (58%) agrees with numbers (55–70%) reported by others [Nguyen et al, ; Neske et al, ; Nicol et al, , ].…”
Section: Discussioncontrasting
confidence: 95%
“…Seroprevalence to MWPyV (84.4%) was the second highest from all of HPyVs tested. Two recent studies reported MWPyV 42–75% in adulthood [Nicol et al, ; Berrios et al, ], which is slightly lower number compared to our findings. Seroprevalence to KIPyV (58%) agrees with numbers (55–70%) reported by others [Nguyen et al, ; Neske et al, ; Nicol et al, , ].…”
Section: Discussioncontrasting
confidence: 95%
“…IMR90 proliferation assays were performed as previously described [60]. Briefly, IMR90 cell lines were seeded in triplicate in 24-well plates (day 0; 5 x 10 3 cells per well).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported the widespread distribution of MWPyV in different areas of the world, including Africa, the USA, Asia, Italy, Australia, and South America [5,[11][12][13][14][15]. In this study, we used a qPCR assay to rapidly and accurately screen for MWPyV in NPA, serum, and fecal samples collected from different populations in China.…”
Section: Discussionmentioning
confidence: 99%